Perbandingan Efektifitas Pelayanan E-Government Melalui Aplikasi Perizinan GAMPIL Di DPMPTSP Kota Bandung Dan Aplikasi Perizinan SAMIRINDU Di DPMPTSP Kabupaten Bandung - Aurelya Aurelya; Ghina Kamila; Revvi Apriani; Raisya Akhwatun Fitra; Geraldy Henry; Andre Ariesmansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research discussed a comparison of two services rendered by local governments that aim to know the effectiveness of government services through licensing applications. As the ages grow, the development of information technology and communications should be put to good use as well as in the services governments provide to their communities through electronic or online media. It is a qualitative study with an approach to case study and a descriptive analysis. According to research, the Bandung government has released 3 applications as a solution to easier the permit. GAMPIL applications can make it easier for small businesses. One door of investment and integrated service (DPMPTSP) of Bandung implementing an electronic service system implemented through Self-print Online Services System (SILONCER) integrated with the SAMIRINDU application. Thus, for the owners of Bandung districts, it is possible to register their efforts to obtain government clearance online. While the application may make it easier for people to obtain permits, it can be said that the implementation has not yet improved their own satisfaction because beyond the quality of human resources, facilities and infrastructure, socialization of communities is less and less widespread. Not only that, the application still has flaws like servers experiencing interference, signal interference and system interference.